Potential Targets and Molecular Mechanism of Quercetin Against Knee Osteoarthritis - Li, Lingling; Huang, Hailiang (Chinese medicine and natural products, 2022)
Objective The objective of this study was to clarify the potential mechanism of quercetin against knee osteoarthritis (KOA) based on network pharmacology and molecular docking.Methods The targets of quercetin were predicted by PubChem and Swiss Target Prediction databases, and the targets of KOA were obtained by DisGeNET, OMIM, and GeneCards databases. Then, the targets of quercetin and KOA were intersected to find the potential targets of quercetin against KOA. The protein–protein interaction network was constructed through the STRING database, and the core targets were screened. Gene ontology (GO) functions enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were performed using DAVID database. The drug–target–pathway–disease network was constructed by Cytoscape software, and the molecular docking verification was performed by Vina.Results There were 49 potential targets for quercetin against KOA, including 10 core targets. GO functions enrichment analysis showed that the biological process of quercetin against KOA mainly involved the negative regulation of apoptotic process, collagen catabolic process, and extracellular matrix disassembly. KEGG pathway enrichment analysis showed that quercetin against KOA was closely related to PI3K-Akt signaling pathway, Rap 1 signaling pathway, FoxO signaling pathway, Ras signaling pathway, TNF signaling pathway, and ErbB signaling pathway. The results of molecular docking showed that the binding energies between ligand and receptors were less than −5 kcal • mol−1.Conclusions The molecular mechanism of quercetin against KOA involves many targets and pathways, which can regulate the proliferation and apoptosis of chondrocytes, degradation of extracellular matrix, and inflammatory reaction. Quercetin can stably bind to the active pockets of core target proteins, thereby exerting the effect against KOA.
Keywords: quercetin; knee osteoarthritis; potential targets; molecular mechanism; network pharmacology; molecular docking